0120 Association Between Sleep Duration and Daytime Memory and Cognition Depends on Sleep Quality: Data from the 2017 Israel Social Survey. (27th May 2020) - Wills, C C; Rosenberg, E A; Perlis, M L; Parthasarathy, S; Chakravorty, S; Grandner, M A
Abstract: Introduction: This study examines the relationship between sleep duration, sleep disturbance, and cognitive problems in a representative sample of the Israeli population. Methods: 7, 230 Israelis responded to an Israeli Bureau of Statistics population-based survey of households from the year 2017. All variables were self-reported. Outcome of interest was difficulty with memory/concentration (none, mild, or severe). Predictors included previous month sleep duration (<=5hrs, 6hrs, 7hrs [reference], 8hrs, or >=9hrs) and sleep disturbance (none [reference], mild [1/week], moderate [2–3/week], or severe [>3/week]). Covariates included age, sex, ethnic group, and financial status. Multinomial logistic regressions evaluated the relationships between variables, and post-hoc testing identified relationships within specific subgroups. Results: 72.9% denied cognitive problems, 22.2% reported mild problems, and 4.9% severe problems. In adjusted analyses, Sleep <=5hrs and >=9hrs were associated with mild (RRR=1.39, p<0.0005), (RRR=1.46, p=0.004) and severe (RRR=2.75, p<0.0005), (RRR=3.24, p<0.0005) cognitive problems, respectively. Mild, moderate, and severe sleep difficulties were associated with mild cognitive problems (RRR=2.09, p<0.0005), (RRR=2.22, p<0.0005), (RRR=2.44, p<0.0005), and severe cognitive problems (RRR=1.77, p=0.001), (RRR=3.04, p<0.0005), (RRR=4.22, p<0.0005), respectively. There was an interaction between sleep duration and sleep difficulties (p<0.05). Among those denying sleep difficulties, only >=9hrs of sleep was associated with cognitive problems. Among those with mild, moderate, and severe sleep difficulties, both short and long sleep were associated with cognitive problems. Conclusion: In an Israeli population sample, both sleep duration and quality were associated with cognitive problems. Among those with sleep difficulties, short and long sleep duration were associated with cognitive problems, but among those denying sleep difficulties, only long sleep was associated with cognitive problems. These results suggest that the impact of sleep loss on real-world cognition may also rely on the presence of poor sleep quality. Support: Dr. Grandner is supported by R01MD011600